Telehealth in Yemen: An overview and a proposed model - Al-Fadhli, Abdulrahman A; Othman, Marini; Rashed, Abdullah; Ramasamy, Ammuthavali (2015)
Yemen’s Health sector has grown significantly gauged from the increasing number of hospitals, health units, health centers, beds and medical staff. Despite the country's direction towards the health sector development and improvement, Yemen ranked poorly in all central factors of health services and access.This paper aims to propose a high level telehealth model which is peculiar to Yemen in terms of its existing health services, culture, geography and ICT readiness.In achieving the aim, a series of interview and document study were conducted to access its ICT potential-infrastructure;rural communication; and available manpower and skill set. It is hoped that implementation of the framework will be able to address the issue.